Vestigios de los prólogos escolares latino-medievales en dos traducciones castellanas cuatrocentistas de Cicerón y Ovidio - Saquero Suárez-somonte, Pilar; González Rolán, Tomás (Cuadernos de Filología Clásica. Estudios Latinos, 2008)
There was a great abundance and variety of the so-called medieval scholar or academic prologues in texts written in latin. Nevertheless, we have found only two examples about Cicero and Ovid in Castilian translations of classical authors written during fifteenth century.